2021
DOI: 10.3389/fpls.2021.767478
|View full text |Cite
|
Sign up to set email alerts
|

Sage Insights Into the Phylogeny of Salvia: Dealing With Sources of Discordance Within and Across Genomes

Abstract: Next-generation sequencing technologies have facilitated new phylogenomic approaches to help clarify previously intractable relationships while simultaneously highlighting the pervasive nature of incongruence within and among genomes that can complicate definitive taxonomic conclusions. Salvia L., with ∼1,000 species, makes up nearly 15% of the species diversity in the mint family and has attracted great interest from biologists across subdisciplines. Despite the great progress that has been achieved in discer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 67 publications
(139 reference statements)
3
17
0
Order By: Relevance
“…sect. Plethiosphace , and their close phylogenetic proximity is supported by molecular evidence (Will & Claßen‐Bockhoff, 2017; Kriebel & al., 2019; Rose & al., 2021). From each population, one or two individuals were sampled in the field by collecting leaf material into silica‐gel.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…sect. Plethiosphace , and their close phylogenetic proximity is supported by molecular evidence (Will & Claßen‐Bockhoff, 2017; Kriebel & al., 2019; Rose & al., 2021). From each population, one or two individuals were sampled in the field by collecting leaf material into silica‐gel.…”
Section: Methodsmentioning
confidence: 99%
“…During the last two decades, several studies demonstrated the paraphyly of this large genus (Walker & al., 2004; Walker & Sytsma, 2007; Will & Claßen‐Bockhoff, 2014, 2017; Kriebel & al., 2020, 2021; Rose & al., 2021), and that the staminal lever evolved independently three (Walker & Sytsma, 2007; Drew & Sytsma, 2012) or five times (Will & Claßen‐Bockhoff, 2017), each time resulting in convergent morphology and function. As a direct consequence of these studies, there is an ongoing debate regarding the exact circumscription of the genus with two major taxonomic treatments proposed, both based on previous studies with extensive molecular and morphological analyses and sampling a large number of taxa: maintaining Salvia with the inclusion of additional 15 species belonging to Dorystaechas Boiss.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations